Preoperative spinal angiography for lateral extracavitary approach to thoracic and lumbar spine. - Champlin, A M; Rael, J; Benzel, E C; Kesterson, L; King, J N; Orrison, W W; Mirfakhraee, M (American Journal of Neuroradiology, 1994)
PURPOSE To establish the safety, efficacy, and value of preoperative angiography in the surgical management of thoracic and lumbar spine disease, in which it is important to avoid injury to the artery of Adamkiewicz or other vessels that supply the spinal cord. METHODS Sixty-one patients were evaluated primarily using digital subtraction angiography, low-osmolar or nonionic contrast agents, selective catheterization limited to the region of disease, and careful angiographic techniques. RESULTS Two minor (small hematomas of the groin) and no major complications of angiography were encountered. Arterial supply to the spinal cord was identified in 22 patients. In 17 patients (77%), the arterial supply was in the region of planned surgery. In each of these patients the surgical approach was altered, either by dictating the use of a posterior surgical approach (four patients) or by altering the side of the lateral extracavitary approach (13 patients). CONCLUSION Spinal angiography is a safe preoperative examination for thoracic and lumbar spine surgery. It is specifically useful when the lateral extracavitary surgical approach to spinal cord decompression and fusion (which predictably interrupts the terminal end-arterial blood supply to the spinal cord, if present) is planned.